Femoral fractures in children - diagnostic approaches, classifications, treatment strategies, and outcomes: a comprehensive review - Čavka, Katarina; Bašković, Marko (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Femoral fractures in children represent a significant injury, accounting for approximately 1–2% of all pediatric fractures. Due to the unique biomechanical and biological characteristics of the growing skeleton, diagnosis, classification, and management differ markedly from adult fractures. This comprehensive review consolidates current evidence on diagnostic approaches, emphasizing the importance of clinical examination complemented by advanced imaging modalities. Various classification systems are discussed to facilitate standardized assessment and guide treatment planning. Treatment strategies are tailored to age, fracture type, displacement, and associated injuries, ranging from conservative methods like casting and traction to surgical interventions such as flexible intramedullary nailing and plate fixation. Outcomes are generally favorable, with high union rates and excellent functional recovery. The article underscores the importance of individualized treatment plans and multidisciplinary management to optimize functional outcomes in pediatric patients. Advances in diagnostic technology and surgical techniques continue to improve prognosis, emphasizing the need for ongoing research to refine management protocols and minimize long-term sequelae in this vulnerable population.